A Model of Tuberculosis Screening for Pregnant Women in Resource-Limited Settings Using Xpert MTB/RIF. (5th October 2011) - Turnbull, Eleanor R.; Kancheya, Nzali G.; Harris, Jennifer B.; Topp, Stephanie M.; Henostroza, German; Reid, Stewart E.
Abstract : Timely diagnosis and treatment of maternal tuberculosis (TB) is important to reduce morbidity and mortality for both the mother and child, particularly in women who are coinfected with HIV. The World Health Organization (WHO) recommends the integration of TB/HIV screening into antenatal services but available diagnostic tools are slow and insensitive, resulting in delays in treatment initiation. Recently the WHO endorsed Xpert MTB/RIF, a highly sensitive, real-time PCR assay for Mycobacterium tuberculosis that simultaneously detects rifampicin resistance directly from sputum and provides results within 100 minutes. We propose a model for same-day TB screening and diagnosis of all pregnant women at antenatal care using Xpert MTB/RIF. Pilot studies are urgently required to evaluate strategies for the integration of TB screening into antenatal clinics using new diagnostic technologies.